Komunikasi Persuasif Konten Youtube Kementerian Agama dalam Mengubah Sikap Moderasi Beragama - Fasha Umh Rizky; Nur Syam (Program Studi Ilmu Komunikasi Fakultas Dakwah dan Komunikasi, UIN Sunan Ampel Surabaya, 2021)
The purpose of this study is to understand how the application of persuasive communication in explaining religious moderation, especially that which is applied to the Youtube content of the Indonesian Ministry of Religion, entitled